Pengaruh Kompetensi Pedagogik dan Profesionalitas Guru terhadap Hasil Belajar Siswa - Ahroza, Mila (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2023)
The purpose of this research to analyze whether there is an influence between pedagogic competence and teacher professionalism, either partially or simultaneously. This research is a quantitative research with path analysis design which is used in testing the direct or indirect effect between research variables. The subjects of this study were teachers and students in the subject of the Qur'an Hadits at MTs in Tembilahan. The data collection used in questionnaire and documentation. And the data analysis that the researcher uses is multiple linear regression analysis. The results of this study are as follows: 1) there is a significant positive effect between teacher pedagogic competence on student learning outcomes by 58.1%; 2) there is a significant positive effect between teacher professionalism on student learning outcomes by 47.9%; 3) there is a significant positive influence jointly between pedagogic competence and teacher professionalism on student learning outcomes by 55.2%.